Marmots and Yersinia pestis Strains in Two Plague Endemic Areas of Tien Shan Mountains - Sariyeva, Gulmira; Bazarkanova, Gulnara; Maimulov, Ravshambek; Abdikarimov, Sabirzhan; Kurmanov, Berzhan; Abdirassilova, Aigul; Shabunin, Anton; Sagiyev, Zaurbek; Dzhaparova, Aigul; Abdel, Ziyat; Mussagaliyeva, Raikhan; Morand, Serge; et al. (Frontiers in Veterinary Science, 2019)
The main purpose of this study was to clarify the role of gray marmots (Marmota baibacina) in the long-term maintenance of highly virulent strains of Yersinia pestis in two plague endemic foci of the Tien Shan Mountains in Kyrgyzstan. We present data from regular observations of populations of M. baibacina and small rodents cohabiting with marmots in the mountainous grasslands of the Sari-Dzhas (east of Issyk-Kul Lake) and the Upper-Naryn (south of Issyk-Kul Lake) natural foci. During 2012-2017, an abundance of marmots and their ectoparasites (fleas and ticks) was significantly higher in Upper-Naryn comparing to Sari-Dzhas, although there were no differences in a number and diversity of small rodents cohabiting with marmots. The plague bacterium was detected either in marmots or their ectoparasites collected during four of six years of observation in Sari-Dzhas and during two of four years of observation in Upper-Naryn. Plague was found in three sectors situated closely to each other in Sari-Dzhas and in one of eight repeatedly surveyed sectors in Upper-Naryn. During 6 years we isolated nine strains of Y. pestis from marmots, two from their fleas Oropsylla silantiewi, one from an unidentified tick, and one from the gray hamster (Cricetulus migratorius). All plague strains isolated from the rodents and their ectoparasites in this study were similar to Antiqua-biovar specific for marmots. The results indicate that plague can circulate continuously in the Tien Shan Mountains in populations of gray marmots and their ectoparasites with a facultative involvement of other rodent species after significant changes in rodent communities that happened in Kyrgyzstan during the previous two decades. The simultaneous field survey of two natural foci of plague, Sari-Dzhas and Upper-Naryn, would be important for further analysis of circulation of Y. pestis strains belonging to Antiqua biovar in the Tien Shan Mountains